Fission cross-section measurement for 238U(n, f)134 ZX reactions induced by D-T neutrons. (May 2019) - Deqing, Niu; Zuoyi, Zhang; Yong, Zhou; Chao, Yang; Yang, Liu; Kaihong, Fang
Abstract: The D-T neutron induced fission fragments from 238 U, i.e ., 134 Te, 134 m I and 134 g I, were measured by low-background HPGe-γ detector. The fission cross-sections of the 238 U(n, f) 134 Te, 238 U(n, f)) 134 m I and 238 U(n, f) 134 g I reactions induced by D-T neutrons, i.e ., 14.7 ± 0.3, 14.5 ± 0.3 and 14.1 ± 0.3 MeV, were measured precisely with the neutron activation technique, where the neutron flux was monitored by accompanying α-particle and the neutron energy was determined by the cross-section ratio of 90 Zr(n, 2 n) 89 Zr to 93 Nb(n, 2 n) 92 m Nb reaction. The fission cross-sections of the 238 U(n, f) 134 Te reaction are 54.3 ± 3.5 mb, 52.6 ± 3.4 mb and 50.0 ± 3.2 mb, corresponding to the above energy points. However, the cross-sections of 238 U(n, f) 134 g I reactions were estimated to be below a value about 8.2 × 10 −3 mb, since almost all the 134 g I nuclide, of which characteristic γ-rays were detected in the spectrum, originated from the 134 Te decay. Meanwhile, the characteristic γ-rays of 134 m I were not found on any spectrum, and beyond the lower limit of measurement. Highlights: Cross-sections of 238 U(n, f)134 Z X reactions by D-T neutrons were measured. Cross-section of 238 U(n, f) 134 Te reaction is around 50 mb with D-T neutrons. Cross-sections of 238 U(n, f) 134m I/ 134g I reactions are estimated to be zero.